Solar Based Automatic Braking System - Muhammad Meidi; Esa Apriaskar; Djuniadi Djuniadi (Praxis : Jurnal Sains, Teknologi, Masyarakat dan Jejaring, 2020)
Solar based automatic braking system. This tool is used as an automatic braking system when a vehicle sees an object in front of it. The HC-SR04 ultrasonic sensor is mounted on a system that is used as an object signal receiver, with Arduino as a control to control motor speed and brakes automatically when seeing an object right in front of the vehicle with a certain distance. The braking is carried out using a PWM speed control system, while the driver used for the motorbike is L298N. as clean energy and reduce waste of costs in the use of electricity, this tool uses solar cells as a power source or as a battery charger.